Grammar-Focused Writing Instruction to the Students’ Writing Recount Text - Safitri, Alvio Arisia; Suharti, Dwi Sloria; Suhendar, Asep (Journal of English Education Studies, 2020)
In learning English, the students often make some problems while building a recount text. One of the problems causing it is that the teacher might use the old teaching method. This research aimed to observe the effect of grammar-focused writing instruction on the tenth-grade students' writing recount text at one of the Senior High School State at Kabupaten Tangerang. The research method used in this research was a quantitative method with a quasi-experimental design by using a non-equivalent control group design. The population of this research was 460 tenth grade students. The sample of this research was taken from two classes that were chosen by using Simple Random Sampling. There were X IPS 4 as the controlled class and X IPS 5 as the experimental class. The normality test result showed that the data is normally distributed, and the homogeneity test result showed that the variants belong to a homogeneous population. The analysis results of post-test by using t-test (The Pooled Variance Model T-test) were obtained data that t-count = 4,37 and t-table = 1,99 with significant level ɑ = 5% or 0,05. From the post-test calculation result, H0 is rejected, and H1 is accepted. It can be concluded that there is a significant effect of students’ writing recount text between students in the experimental class who were taught by using grammar-focused writing instruction and students in the controlled class who were taught by using the conventional method.